Corneal plaque containing levofloxacin in a dog. (24th February 2015) - Park, Young‐Woo; Kang, Byung‐Jae; Lim, Jae Hyun; Ahn, Jung‐Mo; Lim, Hyun Sook
Abstract A 13‐year‐old castrated male Yorkshire terrier developed a corneal ulcer 2 weeks after intracapsular lens extraction (ICLE) in the right eye. The corneal ulcer was treated with levofloxacin eye drops. A plaque with a white luster developed in the central cornea 2 weeks after treatment with levofloxacin eye drops. The corneal plaque was surgically removed under inhalant anesthesia. The corneal plaque displayed antimicrobial activity against Escherichia coli. Furthermore, levofloxacin content in the plaque was confirmed by matrix‐assisted laser desorption/ionization time‐of‐flight/time‐of‐flight (MALDI‐TOF/TOF) mass spectrometry (MS). The corneal ulcer completely resolved 2 weeks after the surgical removal of the corneal lesion and replacement of levofloxacin eye drops with tobramycin eye drops. Although the topical use of levofloxacin is unlikely to lead to corneal chemical deposits due to the high water solubility of the drug compared to other topical fluoroquinolones, this patient developed corneal plaque of the antibiotic drop.